The Effect of Balance and Concentration Exercises on the Shooting Results of Petanque Riau Athletes - Solihin Solihin; Heny Setyawati; Taufiq Hidayah (STKIP Muhammadiyah Kuningan, 2022)
This study aimed to determine and analyze the effect of balance training on shooting results in Riau petanque athletes and the effect of concentration training on shooting results in Riau petanque athletes and investigating the effect of balance training and concentration training on shooting results in Riau petanque athletes. This study uses a quasi-experimental method with the research design